Conceptions of parenthood: ethics and the family - Austin, Michael W. (Ashgate studies in applied ethics, 2007)
Philosophy and the family -- Unsuccessful conceptions of parenthood -- Successful conceptions of parenthood -- Stewardship and parental rights -- Stewardship and parental obligations